Metabolic response of prokaryotic microbes to sporadic hypoxia in a eutrophic subtropical estuary. (May 2020) - Li, Yingdong; Jing, Hongmei; Kao, Shuh-Ji; Zhang, Weipeng; Liu, Hongbin
Abstract: Coastal eutrophication and consequent oxygen depletion (hypoxia) occurs worldwide due to increased human activity. The paucity of genomic information of microbes in hypoxia prone coastal waters have hindered our understanding of microorganism related causation and adaption to the environment. Here, using metagenomic approach, we investigated microbial metabolic capability in heavily polluted Pearl River estuary. Our results highlighted the possible roles of microbial metabolic activity in the formation of bottom water hypoxia by revealing enriched organic degradation related microbial genes in the bottom layer beneath surface phytoplankton bloom. Microbial nitrate reduction in hypoxia layer was low, possibly due to the low pH and fluctuating oxygen level. On contrary, high abundance of sulfate-reducing, and antibiotic and metal resistance related genes were detected in bottom and surface layers, respectively, indicating microbial adaptation to oxygen depletion and pollution. Our study provides gene level information on the interactive relations between microbial functions and environmental stress.